2013
DOI: 10.1080/15588742.2013.739081
|View full text |Cite
|
Sign up to set email alerts
|

(Re)conceptualizing Disability Policy Frameworks

Abstract: American disability policy is often framed as a health, economic, technical, and/or safety issue. This is a critical issue because this specific framework of disability is based upon narrow statutory interpretations of a policy sciences framework rather than a civil rights or social construction framework. This article addresses the critical interpretations of disability policy, notably the Americans with Disabilities Act of 1990 (ADA) and the unintended consequences of the ADA through several court cases. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These theories come from within public policy as well as a host of academic disciplines outside public policy including public administration, public management, political science, sociology, psychology, and a smattering of other fields. Inside of public policy, policy design and social construction theory has been applied with other public policy theories, including: framing (Itkonen, ; Reich & Barth, ), causal stories (Neff, ), policy sciences (Horejes, ), ACF (Weible et al., ), multiple streams (Jensen, ), policy entrepreneurs (Nicholson‐Crotty & Meier, ), punctuated equilibrium theory (Schneider, ), policy tools (Guetzkow, ), path dependency (Soss, ), interest group theory (McCulloch & Wilkins, ), and grid‐group cultural theory (Hoppe, ). Just as some of the previous analysis demonstrates the portability of the theory across substantive contexts, this section's findings are evidence of policy design and social construction's malleability in terms of incorporating other disciplines, theories, and propositions.…”
Section: Analysis Of Past Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These theories come from within public policy as well as a host of academic disciplines outside public policy including public administration, public management, political science, sociology, psychology, and a smattering of other fields. Inside of public policy, policy design and social construction theory has been applied with other public policy theories, including: framing (Itkonen, ; Reich & Barth, ), causal stories (Neff, ), policy sciences (Horejes, ), ACF (Weible et al., ), multiple streams (Jensen, ), policy entrepreneurs (Nicholson‐Crotty & Meier, ), punctuated equilibrium theory (Schneider, ), policy tools (Guetzkow, ), path dependency (Soss, ), interest group theory (McCulloch & Wilkins, ), and grid‐group cultural theory (Hoppe, ). Just as some of the previous analysis demonstrates the portability of the theory across substantive contexts, this section's findings are evidence of policy design and social construction's malleability in terms of incorporating other disciplines, theories, and propositions.…”
Section: Analysis Of Past Applicationsmentioning
confidence: 99%
“…Institutions matter in the social construction and power of target populations. Comparing target populations between countries with different constitutional structures, two studies (Montpetit et al., ; Park & Wilding, ) find that alterations or differences in those structures are drivers of change, while a third (Horejes, ) found that different government institutions develop diverse social constructions of the same target population. Policies from other policy subsystems also influence the social construction or power of target populations (DiAlto, ; Hudson, ; Hudson & Gonyea, ; Jørgensen, ).…”
Section: Analysis Of Past Applicationsmentioning
confidence: 99%